Silence speech in narrative feminist text: Case of Amel Chaouati book: The Algerians of Amboise Castle - Hmida, Abdelkader (Journal of Human Sciences, 2022)
This article attempts to question the silence in the speech in general and in the feminist narrative text in particular, from the book of the Algerian researcher Amal Chaouati entitled "The Algerian Amboise Castle, following the Emir Abdelkader" . This book is a quest for research retracing the history of these five years spent by Emir Abdelkader and his followers. Under house arrest at Amboise Castle, France, an attempt to question the situation of women and children, and to give voice to the silence of women and their stories. It is a multi-disciplinary approach, which attempts to question the theme of silence in an important period in the history of Algeria.